RELEVANSI KOMPETENSI LULUSAN - Pradja, Novi Satria; Chania, Ammar Ammar (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
The University had main of task to prepare profesional scholars. The profile of graduates is a benchmark for the success of an education institution. This is importance to search about trace the development of graduates after finished education as an evaluation of institution. Focus of graduates trace record is the measurement of learning outcome factors with record the profile of graduates divided into three main focus, namely the study period, graduates career, and graduates competent. This research uses a study descriptive qualitative with subject as graduates of the 2016 and 2017 in Faculty of Teacher Training and Education Kuningan University. The data collected instruments used questionnaires and interview guideline. Analysis data, research used techniques that include data reduction, display, and conclusion or verification. The results of the analysis show that the 2016 and 2017 Faculty of Teacher Training and Education from Kuningan University: 1) the average time need to finished study is 8 semesters, 2) 59% from the graduates can relevant work with study and becoming a teacher, and 3) the stakeholders assessing graduates as has sufficient competence. Keywords: Time of Study Period, Career of Graduates, Competent of Graduates